Don Bosco (Journal of Parents and Teachers, 2015)
Don Bosco presents a Salesian educational project that resides in the combination of education and warmth. The creation of a climate, of a temp values which are based on love, warmth and education, using a teaching method that is based on creating circles of interaction that enable personal growth of the student.
Keywords: climate; education; Don Bosco; interaction; educating; affection